Initial experience with minimally invasive extracorporeal circulation in coronary artery bypass graft reoperations - Heinisch, Paul Philipp; Mihalj, Maks; Haliguer, Elif; Gahl, Brigitta; Winkler, Bernhard; Venetz, Philipp; Jenni, Hansjoerg; Schober, Patrick; Erdoes, Gabor; Luedi, Markus M.; Schefold, Joerg C.; Kadner, Alexander; et al. (Swiss medical weekly, 2022)
AIMS OF THE STUDY: Minimally invasive extracorporeal circulation (MiECC) is an established alternative to conventional extracorporeal circulation (CECC) in coronary artery bypass graft surgery (CABG), but data on its use in cardiac reoperations are limited. We aimed to analyse perioperative morbidity and mortality in adult patients undergoing reoperations for isolated CABG using either CECC or MiECC circuits at our centre. METHODS AND RESULTS: In a single centre retrospective observational study of all adult patients undergoing cardiac reoperations for isolated CABG between 2004 and 2016, we identified 310 patients, and excluded those who received concomitant cardiac procedures (n = 205). Of the remaining 105 patients, 47 received isolated redo-CABG using MiECC, and 58 received CECC. Propensity score modelling was performed, and inversed probability treatment analysis was used between the treatment groups. Primary endpoint was 30-day all-cause mortality. Secondary endpoints included major adverse cardiac or cerebrovascular events or need for conversion to CECC. Groups were comparable, apart from a higher incidence of NYHA class III or higher in CECC group (33.5% vs 8.6%, p= 0.004). Shorter times for operation, cardiopulmonary bypass and aortic cross-clamp were observed in the MiECC group. The incidence of postoperative atrial fibrillation was significantly lower with MiECC (22.1%, p = 0.012). No significant difference was observed in all-cause 30-day mortality between the MiECC and CECC groups (6.8% vs. 8.3%, p = 0.81). CONCLUSION: We found no difference in overall mortality between CECC and MiECC in patients undergoing reoperation for isolated CABG. Furthermore, we found no indication of differences in most outcomes between extracorporeal circuit types. In the case of redo-CABG, MiECC could provide an alternative strategy.